The Effect of Independence and Professional Ethics on Auditor Performance at the Bogor Regency Inspectorate - Agung Fajar Ilmiyono; Ellyn Octavianty; Ketut Sunarta; Nabilla Azzahra Pramashella; Suhendra (Institut Bisnis dan Informatika Kesatuan, 2025)
Auditor performance reflects the outcomes of responsibilities such as examining financial statements, assessing compliance, and delivering objective evaluations. Strengthening auditor independence and adherence to professional ethics plays a vital role in sustaining credibility and ensuring accountability in audit outcomes. This study aims to analyse how independence and professional ethics influence internal auditor performance within the Bogor Regency Inspectorate. A verificative approach with an explanatory survey method was applied. The data were obtained from 36 respondents using questionnaires and analysed with SPSS version 29. Descriptive statistics, multiple linear regression, traditional assumption evaluation, and hypothesis testing using the t-test, F-test, and coefficient of determination were among the analytical methods used. The findings suggest that professional ethics and independence have no statistically significant partial effects on internal auditor performance. In a combined test, independence and professional ethics show a considerable positive impact, highlighting their joint contribution in enhancing the quality of internal supervision. These findings emphasise the need for internal auditors to consistently apply independence and professional ethics to improve objectivity, accountability, and the reliability of audit reports. Future research is advised to incorporate other variables such as competence, leadership, and organizational culture to provide broader insights into auditor performance.